2021
DOI: 10.1097/bsd.0000000000001292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of L5-S1 Degenerative Disc Disease on Outcomes of L4-L5 Fusion

Abstract: Objective: The aim was to investigate the clinical relevance of preoperative caudal adjacent segment degeneration (ASD) in patients undergoing isolated L4-5 fusion to determine a threshold of degeneration at which a primary L4-S1 fusion would be warranted.Summary of Background Data: Increased motion and biomechanical forces across the adjacent caudal segment in isolated L4-L5 fusion leads to concerns regarding the increased incidence of revision surgery because of the development of ASD.Methods: Patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…35,36 However, the presence of preoperative disc degeneration did not show a signi cant correlation with the development of postoperative ASD. 37 A study on the degenerative stenosis of the L3-4 intervertebral foramen after L4-5 TLIF surgery can be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 However, the presence of preoperative disc degeneration did not show a signi cant correlation with the development of postoperative ASD. 37 A study on the degenerative stenosis of the L3-4 intervertebral foramen after L4-5 TLIF surgery can be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The disc of L5-S1 is also more prone to degeneration in lumbar fusion and LBP patients [ 34 , 35 ]. However, the presence of preoperative disc degeneration did not show a significant correlation with the development of postoperative ASD [ 36 ]. A study on the degenerative stenosis of the L3–4 intervertebral foramen after L4–5 TLIF surgery can be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our logistic regression analysis also showed that preoperative disc degeneration of Pfirrmann grades IV and V was significantly associated with symptomatic ASD after OLIF at the L4-L5 level and above. However, Conaway et al reported that preoperative disc height ratio and Pfirrmann grading of the L5-S1 level was not predictive of worse clinical outcomes after isolated L4-L5 fusion [34]. This discrepancy could be explained by the distinct degenerative and kinematic properties of the L5-S1 segment compared to the upper lumbar motion segments, which result in re-stabilization in the advanced degeneration of intervertebral disc and facet joints [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, Conaway et al reported that preoperative disc height ratio and Pfirrmann grading of the L5-S1 level was not predictive of worse clinical outcomes after isolated L4-L5 fusion [34]. This discrepancy could be explained by the distinct degenerative and kinematic properties of the L5-S1 segment compared to the upper lumbar motion segments, which result in re-stabilization in the advanced degeneration of intervertebral disc and facet joints [30,34]. Our results also showed that anterior and posterior disc height were not significant risk factors for symptomatic ASD at the L5-S1 level (Table S1).…”
Section: Discussionmentioning
confidence: 99%